Epigenetic Control of Sexual Differentiation of the Bed Nucleus of the Stria Terminalis - Murray, Elaine K. (The Endocrine Society, 2009)
The principal nucleus of the bed nucleus of the stria terminalis (BNSTp) is larger in volume and contains more cells in male than female mice. These sex differences depend on testosterone and arise from a higher rate of cell death during early postnatal life in females. There is a delay of several days between the testosterone surge at birth and sexually dimorphic cell death in the BNSTp, suggesting that epigenetic mechanisms may be involved. We tested the hypothesis that chromatin remodeling plays a role in sexual differentiation of the BNSTp by manipulating the balance between histone acetylation and deacetylation using a histone deacetylase inhibitor. In the first experiment, a single injection of valproic acid (VPA) on the day of birth increased acetylation of histone H3 in the brain 24 h later. Next, males, females, and females treated neonatally with testosterone were administered VPA or saline on postnatal d 1 and 2 and killed at 21 d of age. VPA treatment did not influence volume or cell number of the BNSTp in control females but significantly reduced both parameters in males and testosterone-treated females. As a result, the sex differences were eliminated. VPA did not affect volume or cell number in the suprachiasmatic nucleus or the anterodorsal nucleus of the thalamus, which also did not differ between males and females. These findings suggest that a disruption in histone deacetylation may lead to long-term alterations in gene expression that block the masculinizing actions of testosterone in the BNSTp.